PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PENGEDAR NARKOTIKA MELEBIHI LIMA GRAM YANG DILAKUKAN SECARA TEROGANISASI - anggalana anggalana; Okta Ainita; Ahmad Badawi (Universitas Kapuas Sintang, 2023)
The rise of crime presently could be very worrying to the encompassing network, that is supported with the aid of the rising prices of primary goods which inspire someone so as to make money in a quick way by way of committing crimes along with robbery, robbery, fraud, and selling or dispensing narcotics. from this writing to find out the factors that motive perpetrators to dedicate crook acts of narcotics sellers exceeding five grams that are carried out in an organized way and what's the criminal duty of perpetrators of narcotics dealers exceeding five grams which can be performed in an organized manner. This writing uses a normative juridical approach research technique and qualitative descriptive studies. As for the elements that purpose perpetrators to distribute narcotics, specifically from the outcomes of the research that the authors conducted, the authors concluded that the responsibility of the perpetrators of narcotics dealers turned into to country that Defendant AG became legally and convincingly demonstrated to have committed a crime